Congenital Pulmonary Airway Malformation in Children: Advantages of an Additional Trocar in the Lower Thorax for Pulmonary Lobectomy - Koga, Hiroyuki; Ochi, Takanori; Hirayama, Shunki; Watanabe, Yukio; Ueno, Hiroyasu; Imashimizu, Kota; Suzuki, Kazuhiro; Kuwatsuru, Ryohei; Nishimura, Kinya; Lane, Geoffrey J.; Suzuki, Kenji; Yamataka, Atsuyuki (Frontiers in Pediatrics, 2021)
Aim: To present the use of an additional trocar (AT) in the lower thorax during thoracoscopic pulmonary lobectomy (TPL) in children with congenital pulmonary airway malformation. Methods: For a lower lobe TPL (LL), an AT is inserted in the10th intercostal space (IS) in the posterior axillary line after trocars for a 5mm 30o scope, and the surgeon’s left and right hands, are inserted conventionally in the 6th, 4th, and 8th IS in the anterior axillary line, respectively. For an upper lobe TPL (UL), the AT is inserted in the 9th IS and trocars are inserted in the 5th, 3rd, and 7th IS, respectively. By switching between trocars (6th↔8th for the scope, 4th↔6th for the left-hand, and 8th↔10th for the right-hand during LL and 5th↔7th, 3rd↔5th, and 7th↔9th during UL, respectively), vital anatomic landmarks (pulmonary veins, bronchi, and feeding arteries) can be viewed posteriorly. The value of AT was assessed from blood loss, operative time, duration of chest tube insertion, requirement for post-operative analgesia, and incidence of perioperative complications. Results: On comparing AT+ (n=28) and AT- (n=27), mean intraoperative blood loss (5.6 versus 13.0mL), operative time (3.9 versus 5.1 hours), and duration of chest tube insertion (2.2 versus 3.4 days) were significantly decreased with AT (p<.05, respectively). Differences in postoperative analgesia were not significant. There were three complications requiring conversion to open/mini-thoracotomy: AT- (n=2; bleeding), AT+: (n=1; erroneous stapling). Conclusions: An additional trocar and switching facilitated posterior dissection during TPL in children with congenital pulmonary airway malformation enhancing safety and efficiency.